Synthesis of amorphous trimetallic PdCuNiP nanoparticles for enhanced OER - Zheng, Yangzi; Guo, Ruiyun; Li, Xiang; He, Tianou; Wang, Weicong; Zhan, Qi; Li, Rui; Zhang, Ke; Ji, Shangdong; Jin, Mingshang (Frontiers in Chemistry, 2023)
Metal phosphides with multi-element components and amorphous structure represent a novel kind of electrocatalysts for promising activity and durability towards the oxygen evolution reaction (OER). In this work, a two-step strategy, including alloying and phosphating processes, is reported to synthesize trimetallic amorphous PdCuNiP phosphide nanoparticles for efficient OER under alkaline conditions. The synergistic effect between Pd, Cu, Ni, and P elements, as well as the amorphous structure of the obtained PdCuNiP phosphide nanoparticles, would boost the intrinsic catalytic activity of Pd nanoparticles towards a wide range of reactions. These obtained trimetallic amorphous PdCuNiP phosphide nanoparticles exhibit long-term stability, nearly a 20-fold increase in mass activity toward OER compared with the initial Pd nanoparticles, and 223 mV lower in overpotential at 10 mA cm−2. This work not only provides a reliable synthetic strategy for multi-metallic phosphide nanoparticles, but also expands the potential applications of this promising class of multi-metallic amorphous phosphides.